Beyond Poverty Reduction: Rethinking Inequality and Institutional Justice in Indonesia - Sally Salsabila (Journal of Social Development Studies, 2026)
This article examines the central issue of why poverty reduction in middle-income countries does not automatically lead to a substantive transformation of inequality. Using Indonesia as a strategic case, it analyzes the paradox between declining poverty rates and persistent inequality within an increasingly technocratic development framework. The study adopts a qualitative-interpretive design based on secondary data and policy document analysis, covering World Bank, OECD, and the UNDP Human Development Report as well as successive Indonesian RPJMN documents. The analysis reveals three recurring patterns: first, inequality is framed as a governable development problem through categories such as vulnerability, economic insecurity, and opportunity gaps; second, policy interventions are legitimized through the language of growth, productivity, competitiveness, human capital, and targeting; third, beneficiaries are represented primarily through administrative categories—poor and vulnerable households, the bottom 40 percent, and marginalized groups—rather than as political subjects with voice and rights. These findings show that poverty reduction does not automatically produce substantive equality, particularly when inequality is managed as a technocratic problem rather than addressed as a question of structural justice. The article argues that the central challenge of development lies not only in reducing deprivation, but also in transforming how inequality is framed, justified, and governed. It therefore calls for a shift from inclusive growth toward transformative equality grounded in redistribution, recognition, and representation.